A LINGUISTIC AND LOCAL WISDOM PERSPECTIVE ON BRAND-NAMING IN SMALL AND MEDIUM INDUSTRIES IN BANTAENG - A'ban, Jamaluddin Gesrianto; Putri, Alfridha Dwi; Saleh, Mustakim (RETORIKA: Jurnal Bahasa, Sastra, dan Pengajarannya, 2025)
This study aims to examine brand naming strategies employed by Small and Medium Industries (SMIs) in Bantaeng Regency through linguistic and local wisdom approaches. The research applied a descriptive qualitative method using interviews, observations, and documentation techniques. The findings reveal that SMI actors adopt naming strategies based on local languages, owner personal identity, acronyms, and business philosophy. Elements of local wisdom and cultural identity have been shown to enhance brand value and product competitiveness. Brand naming is not merely a commercial tool but is rich in cultural and spiritual meaning.